Solution-Focused Therapy Program on Self-Esteem and Depression in Thai Older Adults with Major Depressive Disorder: A Quasi-Experimental Study - Phuttharo, Paijit; Suppasri, Jaruwan; Pensuksan, Wipawan Chaoum (Pacific Rim International Journal of Nursing Research, 2025)
Major depressive disorder is one of the most prevalent mental health disorders globally. Older adults represent a particularly vulnerable group, with various factors significantly increasing their risk of developing depression. Thus, they need effective intervention to mitigate this problem. This study employed a quasi-experimental, pretest-posttest control group design to evaluate the effectiveness of the Solution-Focused Therapy Program in enhancing self-esteem and reducing depression among older adults with depression in Southern Thailand. This Program emphasizes solutions rather than problems and focuses on helping individuals identify and utilize their strengths and resources to overcome challenges. Fifty participants were purposively selected and matched based on their depression levels. They were then systematically assigned to either the experimental group (n = 25), receiving the Program, or the control group (n= 25), receiving only usual care. Self-esteem and depression were measured before and after the intervention using the Self-Esteem Scale and the Thai Geriatric Depression Scale, respectively. Data were analyzed using multivariate analysis of covariance. Results indicated that participants in the experimental group exhibited significantly higher median scores on self-esteem and lower depression than those in the control group at one week post-intervention. These findings indicated the Program’s effectiveness in enhancing self-esteem and reducing depression among older adults with depression. Trained nurses can implement this Program to meet the unique needs of this population in clinical practice. However, future multi-site, longitudinal studies are recommended to assess changes in self-esteem and depression over time and evaluate the Program’s long-term impact before widespread implementation in practice.